Double-stage soft x-ray laser pumped by multiple pulses applied in grazing incidence. (28th May 2015) - Ecker, B; Aurand, B; Hochhaus, D C; Neumayer, P; Zielbauer, B; Oliva, E; Li, L; Le, T T T; Jin, Q; Zhao, H; Cassou, K; Daboussi, S; et al.
Abstract: In this paper we report on results obtained with a compact double-stage molybdenum x-ray laser (XRL), operated with a total pump energy of 600 mJ. The two gain regions were pumped using the double-pulse grazing incidence pumping technique, which includes travelling wave excitation for both the seed- and the amplifier-target. In addition, the influence of an additional pre-pulse has been studied. Seeded XRL operation has been demonstrated in both schemes, resulting in XRL pulses with a divergence of 2 × 2 mrad. The peak brilliance of the amplified XRL of 4 × 10 23 photons/s/mm 2 /mrad 2 in 5 × 10 −5 relative bandwidth was more than two orders of magnitude larger compared to the original seed pulses. The presented experimental concept provides an alternative approach to the currently more common use of high-order harmonic pulses as a seed source, well suited for applications like laser spectroscopy of highly-charged ions at a storage ring.